From handicraft to cultural heritage: redefining the role of traditional handicraft in Shanxi's cultural expression - Lyu, Jing; Alli, Hassan; Mohd Yusoff, Irwan Syah; Lyu, Liang (Human Resource Management Academic Research Society, 2024)
This study examines the development of traditional handicrafts in Shanxi from crafts utilitarian to cultural heritage and redefines their role of Shanxi cultural expression. Traditional handicrafts in Shanxi played an immeasurable importance in understanding and explaining the underlying cultural origins. However, traditional handicrafts nowadays have been seriously impacted by the globalization and modernization, especially in the development of productive forces. Industrialized production not only threatens the economic worth of traditional handicrafts, but likewise destroys their cultural value and making the preservation of traditional handicrafts an unprecedented challenge. By analyzing several numbers of traditional handicrafts in Shanxi and understanding their performance Shanxi culture as well as their interaction with cultural heritage, the study acknowledged the role of traditional handicrafts in Shanxi cultural performance has gone beyond the material level to become a vivid and emotional expression of history and culture. At the same time, to ensure the inheritance and development of handicrafts, the joint efforts of the government, education, communities, and craftsmen are needed to protect and promote the development of traditional handicrafts, so that they can flourish back in the hands of outstanding heirs and continue the charm of centuries-old good manufacturing. These findings provide new perspectives that can help to better recognize and protect the valuable intangible cultural heritages.